The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1212/wnl.0000000000004056
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transitions in the epidemiology of stroke and its risk factors in China from 2002 to 2013

Abstract: In 2002-2013, the incidence of stroke in China increased rapidly. Combined with a high prevalence, a trend toward a younger age, and stable mortality, this finding suggests that additional clinical and behavioral interventions for metabolic and lifestyle risk factors are necessary to prevent stroke, particularly in certain populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
167
8
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(196 citation statements)
references
References 28 publications
13
167
8
4
Order By: Relevance
“…Stroke is a leading cause of adult mortality and disability, and there are approximately 3 million new stroke cases every year in China [1,2]. In the past several decades, the incidence of stroke has decreased because of effective strategies for preventing cerebrovascular risk factor and good health services in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a leading cause of adult mortality and disability, and there are approximately 3 million new stroke cases every year in China [1,2]. In the past several decades, the incidence of stroke has decreased because of effective strategies for preventing cerebrovascular risk factor and good health services in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a major cause of death and adult disability (Luengo-Fernandez et al, 2013), and there are approximately 3-4 million new stroke cases every year in China, with roughly 80% being ischemic strokes (IS) (Guan et al, 2017;Jiang et al, 2006;Wang et al, 2007).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Stroke is a major cause of death and adult disability (Luengo‐Fernandez et al, ), and there are approximately 3–4 million new stroke cases every year in China, with roughly 80% being ischemic strokes (IS) (Guan et al, ; Jiang et al, ; Wang et al, ). Atrial fibrillation (AF) is an independent risk factor for IS, and accounts for 10%–25% of all ischemic strokes (Meschia et al, ; Sposato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study demonstrated that the prevalence of proteinuria was higher in the hypertensive group than in the normotensive group (hypertensive group, 33.9%; normotensive, 10%) . Furthermore, data from the China National Stroke Screening Survey (CNSSS) showed that hypertension ranked in first place among factors contributing to stroke in China . The association between proteinuria and stroke, in particular, should be noted in the hypertensive population who are at high risk for the development of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, data from the China National Stroke Screening Survey (CNSSS) showed that hypertension ranked in first place among factors contributing to stroke in China. 8 The association between proteinuria and stroke, in particular, should be noted in the hypertensive population who are at high risk for the development of stroke. More important, proteinuria often changes dynamically, showing regression or progression.…”
Section: Introductionmentioning
confidence: 99%